Adaptations for pressure and temperature effects on loop motion in Escherichia coli and Moritella profunda dihydrofolate reductase. Issue 2 (3rd April 2019) - Huang, Qi; Rodgers, Jocelyn M.; Hemley, Russell J.; Ichiye, Toshiko
ABSTRACT: Determining how enzymes in piezophilic microbes function at high pressure can give insights into how life adapts to living at high pressure. Here, the effects of pressure and temperature on loop motions of Escherichia coli (Ec) and Moritella profunda (Mp) dihydrofolate reductase (DHFR) are compared via molecular dynamics simulations at combinations of the growth temperature and pressure of the two organisms. Analysis indicates that a flexible CD loop in MpDHFR is an adaptation for cold because it makes the adenosine binding subdomain more flexible. Also, analysis indicates that the Thr113-Glu27 hydrogen bond in MpDHFR is an adaptation for high pressure because it provides flexibility within the loop subdomain compared to the very strong Thr113-Asp27 hydrogen bond in EcDHFR, and affects the correlation of the Met20 and GH loops. In addition, the results suggest that temperature might affect external loops more strongly while pressure might affect motion between elements within the protein. GRAPHICAL ABSTRACT: